The Role of The Principal as A Leader at SMKN 1 Bintan Timur - Nela Noviarti; Tedy Roberto; Nurhizrah Gistituati (Bisma The Journal of Counseling, 2022)
The purpose of this study was to determine the role of the principal as a leader in SMKN 1 Bintan Timur. The type of research used is descriptive qualitative. The research subjects consisted of principals, teachers and students. Data were collected through observation, interviews and documentation techniques using the first data analysis technique, namely data reduction, second data collection and then drawing conclusions. The results of the study show the role of the principal as a leader, which refers to the way the principal in mobilizing, directing, guiding, protecting, fostering, setting an example, giving encouragement and providing assistance in order to achieve the school's vision and mission